Destination competitiveness: A phenomenographic study. (February 2018) - Abreu Novais, Margarida; Ruhanen, Lisa; Arcodia, Charles
Abstract: The destination competitiveness literature, while well established, is fraught with inconsistencies over its definition, measurement and its legitimacy as a topic of research. Given the divide that exists, this paper proposes a phenomenographic approach to the study of destination competitiveness. Specifically, the paper argues that efforts to advance destination competitiveness should be preceded by a better understanding of how destination stakeholders is conceptualize the term. This paper explores how destination stakeholders understand destination competitiveness. The findings reveal three distinct conceptions of destination competitiveness which are hierarchically related: destination competitiveness as perception of a destination, destination competitiveness as performance, and destination competitiveness as a long-term process. Additional features of destination competitiveness are discussed including the relationship between competitiveness and attractiveness, and the dynamic nature of the competitor set. This paper concludes with a discussion of the implications for advancing the destination competitiveness concept. Highlights: An outcome space for destination competitiveness with three hierarchically related conceptions is presented. Previously overlooked elements of destination competitiveness are discussed. A unique research approach, phenomenography, is employed.